The Covid-19 pandemic and its impact on the interpretation and implementation of the force majeure clause in international commercial contracts - Alksnis, Eduards Gvido (Riga Graduate School of Law, 2023)
In this thesis, the author analyses the link between force majeure and pandemic prior to Covid-19 and in the light of those findings, the impact of Covid-19 had on the interpretation and understanding of force majeure and pandemics after the Covid-19 pandemic on international commercial contracts. To answer these questions, the author performs qualitative analytical research in all chapters, which in the 3rd chapter are supplemented by a comparative approach. As the focus of the thesis are the contextual and historical approaches on the pandemics and force majeure, these are also the primary prisms through which the paper is viewed and written. The main ideas presented came from the UNIDROIT, ICC, China, USA, etc., which have had the greatest influence and experience with force majeure, pandemics and commercial contracts and provided arguments and considerations for reaching the answer to the presented problems.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Force majeure; Covid-19; Pandemics; Commercial contracts